Uma luz no fim do túnel: avaliação da percepção dos socioeducandos egressos e familiares sobre a aplicação do Sistema Nacional de Atendimento Socioeducativo em uma unidade de semiliberdade - Santiago, Maria Coeli Girão (2014)
With the Constitution of the Federative Republic of Brazil (1988), the Statute of Children and Adolescents - ECA - (1990) and the National System of Socio-Educational Services - SINASE - (2012) provides is sufficient legislation for a guided socio action respect for human rights, from the perspective of inclusion and citizenship. The SINASE regulates the execution of educational measures, establishing the principles and guidelines that should norteá them. The expected socio-educational measures in the ECA, in its art. 120, refers to Socioeducativa Measure Free range. While measure restricting freedom, it has been carried out by the Centre Free range Martyr Francisca, unit constructed in accordance with the SINASE guideline regarding the architectural design and educational proposal. This study presents what is sought to understand how these principles and guidelines are being implemented in educationally childcare service in Free range Martyr Francisca Center. So problematized is the hybrid character of socio-educational measures, raising questions about their sanctioning and educational content as well as the subjective and microsocial forms of everyday life involving adolescents in compliance with socio-educational measures of semi-liberty in Fortaleza. Thus, this work is conceived as a process of evaluation, using the qualitative methodology, based on the case study method. Through it, one can understand the perceptions and meanings of social and educational services in the design of its most legitimate recipients: the socioeducandos and their families. The instruments used for data collection is consisted of: desk research, routine observations, semi-structured interviews, medical records and records in Individual Care Plans. This study will establish a pedagogical relationship mediated by means other than punitive, composing a new look at the socioeducandos, and them about themselves; It points out the need and the difficulty does not have an Alumni Program; and demonstrates the need for a greater involvement of the state executive power, in achieving the goals established in the State Plan for Socio-Educational Services.